Hot air‐assisted radio frequency drying of apricots: Mathematical modeling study for process design. Issue 2 (20th January 2022) - Topcam, Huseyin; Gogus, Fahrettin; Ozbek, Hatice Neval; Elik, Aysel; Yanik, Derya Kocak; Dalgic, Ali Coskun; Erdogdu, Ferruh
Abstract : Abstract: Conventional hot air and solar energy processes have been used for apricot. These processes had adverse effects on the quality due to the longer process times, and this indicates the need for an innovative approach. Radio frequency (RF) processing has innovation potential for drying with its volumetric heating feature, but an optimal process should be designed for process efficiency in industrial‐scale applications. Therefore, the objective of this study was to confirm the RF process for industrial‐scale apricot drying. For this purpose, a mathematical model was developed to predict temperature and moisture content change of apricots during drying, and experimental validation study was carried out. For the RF drying process, pre‐dried apricots (0.58–0.75 kg water/kg dry matter, db) by solar energy were used. The purpose was to start the RF process at a suitable moisture content level as this process was not feasible to apply directly due to the high initial moisture content of apricots (up to 4 kg water/kg dry matter, db). RF drying experiments were carried out in a 10 kW hot air‐assisted (50–60°C) staggered through electrode system. Optimum electrode gap was 81 mm with 2500 V potential of the charged electrode. Final moisture content of the dried apricots was 0.25–0.33 kg water/kg dry matter (db). Following the model validation for temperature and moisture content change, industrial‐scale apricot drying scenarios were demonstrated to confirm the RF process for feasibility and process design. Practical Application: A comprehensive mathematical model was developed for radio frequency (RF) drying of apricots. This model was experimentally validated with respect to the temperature and moisture content change. Various process design studies were carried out for an industrial‐scale apricot drying process to confirm the process feasibility. With this background, the results of this study can be directly used in an industrial drying for an optimal process design and energy efficiency.